PENGGUNAAN MEDIA WORDWALL DALAM PEMBELAJARAN TEKS CERITA INSPIRATIF SISWA SMP KELAS IX - Violetta Intan Rahmatika; Ika Septiana (Bahasa Indonesia Prima, 2024)
The development of the current era makes humans dependent on technology. Advances in information technology have an influence on its users, both positive and negative influences. Technological developments play an important role in the field of education. In the world of education, the use of technology needs to be used in the learning process. Students are more interested in the learning process that utilizes game-based learning media. There are many game-based learning media that can be used by teachers, one of which is Wordwall. However, in practice, students often find themselves taking advantage of the opportunity to access other things that are not related to the learning being provided. This article aims to determine the factors that influence the use of Wordwall media in learning Inspirational Story Texts for class IX junior high school students. This research was conducted with a qualitative descriptive approach. Data collection techniques in this study were in the form of observation and interviews. The object studied is the factors that influence the use of Wordwall media in learning Inspirational Story Texts for class IX Junior High School students.